Smartphone use and personality: Their effects on sleep quality across groups using mediation analysis - Tauseef Ur Rahman; Zahoor Jan; Aftab Alam; Raian Ali (Digital Health)
Purpose The rapid rise in smartphone use has led to declining sleep quality. Excessive internet use has been linked to negative impacts on physical and mental health, and individual personality traits (PT) may contribute to internet addiction and mitigate its harmful effects. This study aims to: (1) examine whether PT mediate the relationship between smartphone use and sleep quality, and (2) investigate whether the relationship between smartphone use and sleep quality varies across different gender and age groups. Methods There were 269 participants in the dataset. The daily averages for sleep duration, sleep distraction, and smartphone use were extracted from the usage data acquired through a dedicated smartphone application. Structural equation modeling was employed to investigate the mediating role of personality in the relationship of smartphone use and sleep quality. Results Results indicated that PT partially mediated the relationship, with a significant negative indirect impact of smartphone use on sleep quality. Age differences were observed, showing distinct patterns between younger and older participants, while no significant gender differences emerged. Conclusions This study found that excessive smartphone use, coupled with low personality indicators, leads to poor sleep quality. Positive personality traits improve sleep outcomes, with age influencing the impact of smartphone use on sleep. Our findings support and contribute to existing concerns about technology overuse and highlight the need for targeted interventions to promote more beneficial technology design and usage patterns.